Toward Identification of Disco Regulatory Proteins via Genetic Interaction Screens - Boszko, Marta (My University, 2000)
The Disco protein has been identified as a transcription factor involved in the development of the 𝘋𝘳𝘰𝘴𝘰𝘱𝘩𝘪𝘭𝘢 𝘮𝘦𝘭𝘢𝘯𝘰𝘨𝘢𝘴𝘵𝘦𝘳 nervous system (Steller et al., 1987; Heilig et al., 1991; Lee et al., 1991). Although, its loss of function phenotype is well characterized, the specific function of Disco in development remains unknown. One method of elucidating the role of 𝘥𝘪𝘴𝘤𝘰𝘯𝘯𝘦𝘤𝘵𝘦𝘥 is to identify additional signaling components with which it interacts. The GAL4-UAS system (Brand and Perrimon, 1993) was used to create gain of function mutant phenotypes of the embryonic central nervous system, larval visual system and adult compound eye. These dominant phenotypes had in common perturbations in cell differentiation and axonogenesis. Thus, these dominant phenotypes have provided an opportunity for further genetic interaction screens that would lead to the identification of proteins that interact with Disco. A putative binding site for Disco itself, called s120, has been identified in the 5' flanking region of the 𝘥𝘪𝘴𝘤𝘰 locus (Lee et al., 1999). To discern whether tissue-specific Disco expression is regulated by this sequence, we utilized a promoter-𝘭𝘢𝘤𝘡 fusion that included this regulatory sequence. The germ-line transformant lines carrying this construct showed β-galactosidase expression patterns that resembled wildtype 𝘥𝘪𝘴𝘤𝘰 expression, both in embryos and in the larval central nervous system (previously described by Lee et al., 1991). The expression of β-galactosidase remained like wildtype in the presence of excess Disco protein. Thus, this s120 regulatory sequence and the 5' flanking region studied were not sufficient to regulate Disco expression in the optic lobe primordium. Upon sequencing and analysis of this region, several transcription factor binding site consensus sequences were identified. These sequences, as well as others, may be required for interaction with Disco to confer tissue-specific autoregulation. Further sequencing and expression from deletion constructs is necessary to identify additional 𝘤𝘪𝘴-acting regulatory regions of Disco.
Keywords: disco proteins; genetics